Specific antibody-dependent killing of Toxoplasma gondii by normal macrophages. - Anderson, S E (1976)
The requirement for specificity of antibody-dependent inhibition or killing of intracellular Toxoplasma gondii trophozoites by normal mouse peritoneal macrophages was evaluated in vitro using light microscopy and autoradiography. Anti-toxoplasma antibody in the presence of 'accessory factor' rendered extracellular T. gondii trophozoites non-viable and non-infectious for cells, whereas exposure of extracellular trophozoites to heat-inactivated immune serum did not appear to damage the parasites. Although pretreatment of extracellular trophozoites with heat-inactivated immune serum neither diminished nor prevented infection of normal mouse peritoneal macrophages, it did confer upon macrophages the ability to inhibit or kill the organisms once they were intracellular. In contrast, pretreatment of trophozoites with either heat-inactivated normal or Besnoitia jellisoni immune serum did not enable normal macrophages to inhibit or kill T. gondii; rather, such organisms multiplied intracellularly in normal macrophages. Thus, pretreatment with specific antibody alone prepared T. gondii trophozoites for intracellular destruction by normal mouse peritoneal macrophages. These results suggest that spesific antibody acting in concert with normal macrophages may play a role in controlling infection with T. gondii.